Effect of different particulate types on the properties of rice composite - Asoon, L. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Rice husk, stem and straw are by-products as of rice milling process. However, they can be economically utilized to generate energy, used as bedding materials for animals or burnt as land filling. Another alternative is to use these by-products as reinforcing materials to produce rice bio composites with promising potential. This project focuses on the potential of rice husk, stem and straw to produce composite materials by investigating the mechanical properties of the composites. Particles of rice husk, stem and straw were used as reinforcing fillers while polypropylene was used as matrix. The preparations as well as testing of specimens have been carried out according to ASTM D 638 for tensile test and ASTM D 790 for three point bending or flexural test. The results from this project show that rice bio composites are indeed have the potential to produce materials with good mechanical properties. Rice husk composites which have 8.23 MPa of Ultimate Tensile Strength, 0.79 GPa of Young’s Modulus and 32.64 MPa of flexural strength proves to be the most versatile material out of those byproducts. However, other parts of paddy such as stem and straw should not be ignored considering that the mechanical properties of composites produced from these parts are also acceptable. Somehow, the combinations of different parts of rice to produce composite are beneficial and economically profitable based on the fact that these parts are usually thrown away after milling process has been done.